The implication of syllabification on the use of comparative and superlative adjectives in essay writing - Subajana, J. (University of Jaffna, 2020)
Adjectives are one of the main parts of speech of the English language, although historically they were classed together with nouns. Adjectives play a significant role in grammar and writing. The comparative and superlative adjectives are formed based on the word syllable. Depending on the syllables, the form may differ. Using adjectives in writing is a challenge for many ESL students. The students of the Faculty of Business Studies, Vavuniya campus, find it challenging to use the forms correctly. This paper investigates incorrect forms of comparative/superlative forms in the “compare and contrast” essays written by the students during the first-year English course. The research problem is why ESL learners find it challenging to use the above forms in their writing, although they have learned and known the relevant rules for years. The objective is to draw attention to their use. The data were collected from direct classroom observations, interviews, and structured questionnaires administered to 50 students. They were analyzed both qualitatively and quantitatively. The findings show that (1) the students are not aware or not clear of the demarcation of the syllabic systems such as mono-syllabic, di-syllabic or poly-syllabic because the forms of adjectives vary based on the number of the syllables, (2) they do not incorporate the grammar rules in their writing to overcome these challenges and( 3) there is no knowledge of the relevant suffixes and the placement of the definite article ‘the’ in the superlative form. Further, the mother tongues, Tamil and Sinhala, do not have specific comparative, superlative markers based on the syllables as in the English language. These are some of the other reasons which have been discussed in detail in the paper for the malformations of the adjectives. Thus, this study recommends specific strategies to improve teaching and learning the degrees of adjectival use.
Keywords: Comparative and superlative adjective; Compare and contrast essay; Contrastive analysis and suffix